2013
DOI: 10.1097/md.0000000000000010
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Involvement in Whipple Disease

Abstract: Whipple disease (WD) is a rare multisystemic infection with a protean clinical presentation. The central nervous system (CNS) is involved in 3 situations: CNS involvement in classic WD, CNS relapse in previously treated WD, and isolated CNS infection. We retrospectively analyzed clinical features, diagnostic workup, brain imaging, cerebrospinal fluid (CSF) study, treatment, and follow-up data in 18 patients with WD and CNS infection.Ten men and 8 women were included with a median age at diagnosis of 47 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 28 publications
1
29
0
2
Order By: Relevance
“…Depending on the location of the lesions, symptoms can be both central or peripheral and either isolated or multifocal. Symptoms associated with Whipple's disease range from abnormal movements (myoclonus, choreiform movements, oculomasticatory myorhythmia), hypersomnia, coma, ophthalmoplegia, cognitive impairment, frontal lobe syndrome, cerebellar ataxia, or upper motor neuron and extrapyramidal symptoms (127). It has even been suggested that there is a relation between T. whipplei infection and the development of Parkinson's disease (117,128,129), but it is unlikely that there is a causative relation.…”
Section: Classic Whipple's Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Depending on the location of the lesions, symptoms can be both central or peripheral and either isolated or multifocal. Symptoms associated with Whipple's disease range from abnormal movements (myoclonus, choreiform movements, oculomasticatory myorhythmia), hypersomnia, coma, ophthalmoplegia, cognitive impairment, frontal lobe syndrome, cerebellar ataxia, or upper motor neuron and extrapyramidal symptoms (127). It has even been suggested that there is a relation between T. whipplei infection and the development of Parkinson's disease (117,128,129), but it is unlikely that there is a causative relation.…”
Section: Classic Whipple's Diseasementioning
confidence: 99%
“…Symptoms like diarrhea, joint pain, and fever usually disappear within a week, while other symptoms may take several weeks to disappear (33,62,102,106). It is difficult to cure patients with late symptoms like eye, heart, and CNS involvement, and these patients tend to have high relapse and mortality rates (33,62,125,127,130). Sometimes patients with early symptoms are also hard to treat, as they seem to suffer from lifetime infection either due to permanent carriage of the bacteria in a niche in the patient where it is difficult for the antibiotics to eradicate the bacteria, the development of resistance against these antibiotics, or by reinfection (41,199).…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymerase chain reaction (PCR) of the cerebrospinal fluid (CSF) is confirmatory in patients with isolated CNS-WD. 5 MRI of the brain can show tumorlike or multifocal lesions in the midbrain, thalamus, and temporal lobe, 5 or signal abnormalities in the middle cerebellar peduncle (Fig. 1).…”
Section: Whipple Diseasementioning
confidence: 98%